2009
DOI: 10.2165/11310860-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Potential Influences of Complementary Therapy on Motor and Non-Motor Complications in Parkinsonʼs Disease

Abstract: Nearly two-thirds of patients with Parkinson's disease (PD) use vitamins or nutritional supplements, and many more may use other complementary therapies, yet <50% of patients have discussed the use of these complementary therapies with a healthcare professional. Physicians should be aware of the complementary therapies their patients with PD are using, and the possible effects of these therapies on motor and non-motor symptoms. Complementary therapies, such as altered diet, dietary supplements, vitamin therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 131 publications
0
36
0
Order By: Relevance
“…[6][7][8] The purpose of this study was to determine the effects of a long-term community-based dance program in people with PD, with all evaluations conducted off medication. As evidence emerges suggesting that exercise may positively impact multiple dimensions, 9 and with recent animal studies suggesting exercise may have neuroprotective effects in PD, 10 we were interested in the effects of dance on disease progression as assessed by our primary variable, the Movement Disorder Society-Unified Parkinson Disease Rating Scale 3 (MDS-UPDRS-3). We hypothesized that: 1) the Tango group would demonstrate improvements in disease severity and physical function not noted in the Control group and 2) Tango participants would show larger improvements in function at 6 and 12 months compared to 3 months.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] The purpose of this study was to determine the effects of a long-term community-based dance program in people with PD, with all evaluations conducted off medication. As evidence emerges suggesting that exercise may positively impact multiple dimensions, 9 and with recent animal studies suggesting exercise may have neuroprotective effects in PD, 10 we were interested in the effects of dance on disease progression as assessed by our primary variable, the Movement Disorder Society-Unified Parkinson Disease Rating Scale 3 (MDS-UPDRS-3). We hypothesized that: 1) the Tango group would demonstrate improvements in disease severity and physical function not noted in the Control group and 2) Tango participants would show larger improvements in function at 6 and 12 months compared to 3 months.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary evidence suggests that it may also influence non-motor symptoms of PD, such as respiratory disorders, gastrointestinal disorders, mood disorders, sleep and orthostatic hypotension. Whenever possible, clinicians should ensure that complementary therapy is used appropriately in PD patients without reducing the benefits of dopaminergic therapy 125 . Strategy based on melatonin supplements has been proposed to at risk parents of schizophrenia to eliminate the disorder 126 .…”
Section: Melatonin and Neurological Conditionsmentioning
confidence: 99%
“…The broadest application has been in the treatment of shift work and other sleep disorders (Thorpy, 2010). Preliminary evidence has suggested that BLT may influence depression, primary sexual dysfunction, and nonmotor symptoms of Parkinson's disease (Bossini et al, 2009;Freeman, 2009;Zesiewicz & Evatt, 2009). However, contraindications are not yet fully understood (Wu & Swaab, 2007).…”
Section: Background Literaturementioning
confidence: 99%